Vivi : a biography of Vivienne Goonewardena - Liyanage, Pulsara (Colombo : Women's Education and Research Centre, 1998)
Biography of a political leader from Sri Lanka.
Keywords: Politicians -- Sri Lanka -- Biography; Sri Lanka -- Politics and government. -- women in politics -- left movement